Over a million students use our free study notes to help them with their homework
We add the two equations together (left-hand sides and right-hand sides separately). By doing this we get: 2x + y + (x - y) = 12 + 6. By rearranging and simplifying: 3x = 18.If we divide both sides by 3 w...
To simplify the fraction first notice (1-x2) = (1-x)(1+x) so the common factor of (1+x) in the numerator and denominator can be cancelled. (1+x)/((1-x^2)(2x+1)) = 1/((1-x)(2x+1)), then we need ...
Rearrange to (74)2 = ((72)2)272 = 49(72)2 = 492 = (50-1)2 = 502 - 2x50 + 1 = 24017<...
The total amount of student would be represented by 1 or 100%. The pupils are split into three categories meaning the total must add up to 1. Therefore to find the remaining pupils who walked to school we...
←
385
386
387
388
389
→
Internet Safety
Payment Security
Cyber
Essentials